There and back again in the Rawah Wilderness: reoccupation at high elevations in the Medicine Bow Mountains, Colorado - Buckner, Paul H., author; LaBelle, Jason M., advisor; Van Buren, Mary, committee member; Carr Childers, Leisl, committee member (Colorado State University. Libraries, 2020)
This thesis considers the role of reoccupation and persistent use of place in broader systems of high elevation landscape use in the Southern Rocky Mountains. With a geographic focus on the Medicine Bow Mountains of northern Colorado, the study identifies substantive patterns in the assemblage composition, landscape distribution, and surface structure of sites exhibiting evidence of high reoccupation intensity. Following a laboratory analysis of 2,372 artifacts from 30 sites, as well as high resolution mapping of surface artifact distributions in the field, the study identifies several trends with significant potential for clarifying understandings of the precontact utilization of these landscapes. First, a substantial range of reoccupation intensity exists in the surface record of the Medicine Bow Mountains. Second, sites with evidence of preferential reoccupation exhibit significant variability in their assemblage composition, likely reflecting the diverse range of functional activities and transhumance systems associated with their use through time. Third, spatioenvironmental modeling of reoccupation at the landscape scale suggests high elevation contexts, particularly the timberline ecotone, were a focal point of persistent reuse in the study area. Fourth, the surface record of persistently reused places constitutes a palimpsest of time-averaged deposits from many discrete occupations. Analysis of the spatial character and composition of these deposits informs broader understandings of the structure of these sites and the reconstruction of their long-term use through time. These results reinforce the archaeological significance of the Medicine Bow Mountains for clarifying larger patterns in the indigenous use of high elevations in Colorado.
Keywords: hunter-gatherer archaeology; maximum entropy modeling; persistent places; landscape archaeology; high elevation archaeology; Medicine Bow Mountains